PS-101 Risk management of HBV reactivation in haematological patients treated with rituximab. (24th March 2015) - Tristancho, A; Fobelo, MJ; Artacho, S; Jimenez, CJ; Alvaro, S; Manzano, M; Gomez, E; Guzman, MI; Haro, C
Abstract : Background: Treatment with rituximab may cause reactivation of hepatitis B virus (HBV). Purpose: To find out if HBV serology for patients with haematological diseases treated with rituximab is routinely performed in accordance with the HBV reactivation prophylaxis protocol. According to the results, to develop a strategy to ensure compliance with the protocol. Material and methods: Observational, retrospective study of haematological patients who started treatment with rituximab between December 2012 and April 2014. The HBV reactivation prophylaxis protocol requires patients to be screened before starting treatment with rituximab and, depending on the serological results, the recommendations of the European Association for Study of the Liver and Asociación Española para Estudio del Hígado are to be followed. The following data were collected: date of initiation of treatment with rituximab, date and results of serology (HBsAg, anti-HBc, viral DNA). Results: 96 patients were included. The protocol was not followed in 24 patients (25%). Non-compliance was due to no screening for HBV in 21 patients (22%). The remaining 3 patients (3%) were anti-HBc positive and in one of them the viral load was not determined. Furthermore, none of the 3 received the recommended prophylactic treatment required because they were anti-HBc positive. We therefore propose making the proper HBV screening and monitoring of all patients treated with rituximab an essential requisite prior to the pharmaceutical validation. This is to ensure that the serological profile of HBV is available and that preventive actions and treatments have been carried according to the serology results. Conclusion: The risk of reactivation of HBV is due to: absence of HBV serology and absence of viral DNA levels and/or recommended prophylactic treatment according to the protocol. The proposed strategy to prevent HBV reactivation is to include serological profiling as a requirement for pharmaceutical validation of those patients treated with rituximab. Reference: Hoofnagle JH. Reactivation of hepatitis B. Hepatology 2009;49:S156–65 No conflict of interest.